'Universal' representation of HPGe detector efficiencies. (November 2016) - Findlay, D.J.S.
Abstract: By fitting a simple 4-parameter function to twelve sets of HPGe detector efficiency measurements, an approximate 'universal' expression good to ±15% is obtained for HPGe absolute full-energy-peak efficiencies as a function of photon energy between ∼125 and ∼1750 keV for a ∼4-to-1 range of crystal volumes and for coaxial and planar crystal shapes. Highlights: An approximate 'universal' HPGe absolute photopeak efficiency function is proposed. The function covers a ∼4-to-1 range of crystal volumes, and coaxial and planar crystals. The function is good to ±15% on average between 125 and 1750 keV.